The effectiveness of parent participation in occupational therapy for children with developmental delay - Lin CL (Dove Medical Press, 2018)
Chien-Lin Lin1,2 Chin-Kai Lin,3 Jia-Jhen Yu4 1Department of Physical Medicine and Rehabilitation, China Medical University Hospital, 2School of Chinese Medicine, College of Chinese Medicine, China Medical University, 3Program of Early Intervention, Department of Early Childhood Education, National Taichung University of Education, 4Occupation Therapy Unit of Rehabilitation Techniques Section, Lin Shin Medical Corporation Wuri Lin Shin Hospital, Taichung, Taiwan Introduction: This study aims to explore the impact of Parent Participation Program on the development of developmental delay children. Methods: Pretest-posttest equivalent-group experimental design study was used in this paper. A total of 30 pairs of developmental delay children aged 0–72 months and their parents participated into this study. They were divided into two groups, namely control group and experimental group, according to parents’ wishes. The objects of study in control group received 16 courses of direct rehabilitation therapy; those in experimental group received 8 courses of direct rehabilitation therapy and 8 courses of instruction and tracking of Parent Participation Program. The duration of the intervention was 8 weeks. All cases should be evaluated before and after the intervention, to analyze the difference before and after intervention and among groups. The statistical methods in this paper included descriptive analysis, Chi-square test, independent sample t-test, pair-sample t-test. Results and conclusion: The intervention of Parent Participation Occupational Program has positive impact on the development of developmental delay children in various fields. Among all the intervention results, the progress of the experimental group is 1.895 times more than that of the control group. With parent involvement, Parent Participation Occupational Therapy can promote the cognitive ability, language ability, action ability (gross and fine movement), social competence and self-care ability of children with developmental delay. Finally, the researcher presents suggestions and directions for future research in accordance with the results. Keywords: early intervention, preschool, developmental delay